Esophageal Melanocytosis as a Rare Disease of Esophagus - Balamir, Melek; Eşkazan, Tuğçe; Önal, Uğur; Candan, Selçuk; Ekşi, Onur; Ceyran, Ayşe Bahar; Dobrucalı, Ahmet Merih (Cerrahpaşa Medical Journal, 2024)
Esophageal melanocytosis is an extremely rare condition characterized by melanocyte proliferation in the esophageal squamous epithelium. The etiology and pathogenesis of the disease are unclear. Although it is thought to be a benign condition, there are publications reporting that it may be a precursor of malignant melanoma. In this report, we present a case with esophageal melanocytosis along with a literature review. Cite this article as: Balamir M, Eşkazan T, Önal U, et al. Esophageal melanocytosis as a rare disease of esophagus. Cerrahpaşa Med J. 2024;48(1):105-107.